Ireland : Third Review Under the Extended Arrangement: Staff Report; Letter of Intent; Memorandum of Economic and Financial Policies; Technical Memorandum of Understanding; Letter of Intent and Memorandum of Understanding on Specific Economic Policy Conditionality (College of Commissioners);Staff Supplement; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2011)
The Irish authorities steadfastly maintained strong policy implementation despite a sharp escalation and expansion of stress in euro area sovereign bond markets. Strengthened European support is welcome, but early implementation is key, and restoring broader stability in the euro area is essential. Strengthening supervision and the broader financial framework is critical. Lowering the interest rates on EU loans, and lengthening their maturities, will improve debt and debt service dynamics. Timely and sound implementation of financial sector reforms will help to fully benefit from stronger European support.